Analisis Manajemen Risiko Pada Perusahaan Perbankan Yang Go Public - Deograsias Yoseph Y.F. (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2018)
The expanding banking growth is followed by the increasing number of risks that must be faced by banks. Along with the external conditions of the banking sector which were increasingly troubled by the threatening risks, Bank Indonesia required each bank to have an integrated risk management system. To minimize this risk, Basel II is applied to improve the standards for banks that go public in order to manage risk management properly. As a financial intermediary, the implementation of risk management is very important for banks to reduce losses. Maximum risk management for banks can ensure banks will survive destruction if a bad situation occurs. With the increasingly complex risks in the banking industry, Good Corporate Governance practices are needed. These efforts are carried out to avoid a banking crisis in the future.